(untitled) (Archaeologia Adriatica, 2023)
In 2015, the University of Zadar and the University of Maine (USA) launched a systematic program of research at the Nadin-Gradina site. Five test probes were initially scattered within the area of the settlement defined by the so-called megalithic rampart to document depth, chronological sequence, and integrity of the archaeological record. Preliminary results demonstrate a complex cultural stratigraphy that, in some probes, exceeds 2 meters in depth and confirms the intense development of an urban community that occupied Nadin-Gradina during the Iron Age and Roman era. The investigated portion of the flat necropolis suggests the presence of an Early Iron Age settlement although its archaeological confirmation is still missing. In the Late Iron Age, a wider area of the settlement was used, which seems to mostly correspond to the ancient dimensions of the settlement. The most significant physical transformation of the settlement is associated with the onset of the Roman phase of Nadin’s history, when it acquired the status of the Roman municipium Nedinum. At the end of Late Antiquity, the settlement was abandoned, only to regain importance during the Late Middle Ages and Early Modern Era. At this time, a fort was built on the summit area, which fell under the authority of the Venetians, and subsequently the Ottomans. Its ruins are preserved up to a height of several meters and dominate the present-day view of the site.